Sharia Economic Law Perspective on the Contractual Use of Indonesian Standard QR Code (QRIS) in Digital Transactions - Nurkhofifah, Siti; Marwin; Kurniati, Herlina (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the validity of contracts in the Indonesian Standard Quick Response Code System (QRIS) from the perspective of Islamic economic law, as a response to the epistemological challenges of digital transformation to classical contract theory. The digitalisation of economic transactions has introduced new complexities in the application of the pillars and conditions of contracts as understood within the framework of conventional fiqh muamalah, thus requiring a conceptual reinterpretation of the ijab-qabul mechanism, the concept of majlis al-’aqd, and the validity of non-verbal contract forms. The emergence of QRIS as a national payment standard developed by Bank Indonesia is not only a technological innovation in supporting financial inclusion and economic digitalisation, but also raises fundamental questions about the validity of multi-party contract structures in the digital payment ecosystem in accordance with sharia principles. This study uses a descriptive qualitative method with a field research approach that integrates inductive thematic analysis, document review based on the fiqh muamalah framework, and structured participatory observation. Data were obtained through in-depth interviews with business actors who use QRIS, Muslim consumers, and muamalah academics, and were reinforced with literature related to Islamic economic law and Bank Indonesia regulations. The results of the study indicate that the main contract formed in QRIS transactions is a sale and purchase contract (ba’i), while additional contracts include wakalah between business actors and service providers, as well as ijarah in the context of payment processing services. From a Shariah perspective, QRIS is in accordance with the principles of an-taradhi (mutual agreement), al-’adalah (fairness), and la dharar wa la dhirar (no harm), particularly due to its cost transparency and consumer protection. The scientific contribution of this research lies in the development of a framework for analysing digital contracts based on maqasid Shariah, which combines classical contract theory with the reality of contemporary electronic transactions, resulting in the conceptualisation of “virtual assemblies” and “digital consent” as a form of evolution of the pillars of contracts in the context of financial technology. These findings enrich the treasury of fiqh al-nawazil (contemporary fiqh issues) by providing sharia justification for digital economic practices that were previously in the grey zone of Islamic law, while also providing normative guidance for the future development of sharia fintech products. Therefore, the use of QRIS can be declared valid according to Islamic economic law and has the potential to become a model for digital payment instruments that are in accordance with the principles of Islamic muamalah.